Mindfulness And Rehabilitation: An Evaluation In Routine Clinical Practice. (1st April 2019) - Milner, Victoria; Edwards, Allison; Bell, Victoria
Aims: This Study Investigated the Feasibility of a 5-session Mindfulness-based Group, Including Patient Perceptions and Experiences; Background: Mindfulness Interventions Help Individuals to Purposefully Pay Attention in the Present Moment Whilst Adopting a Non-judgmental Approach. Mindfulness Primarily Focuses on How People Relate with and Respond to Their Experiences, Rather Than Directly Challenging Them. Previous Research Has Explored the Effectiveness of Mindfulness Interventions in Mood Disorders, But There Is Limited Evidence on the Use of Mindfulness-based Groups for Patients on Rehabilitation Wards Who Typically Have Chronic, Complex and Co-morbid Disorders; Methods: All Patients (n = 21) on One Inpatient Rehabilitation Ward Were Invited To Five, Weekly Group Mindfulness Sessions. Pre and Post-session Self-rated Measures of Stress and Calm Levels Were Recorded. Semi-structured Interviews Were Independently Conducted with Participants Following the Group, to Obtain Feedback, Which Were Transcribed and Thematically Analysed; Results: 11 Patients Attended at Least One Group Session. Scores from Post-group Measures Indicated an Increase in Calmness and Reduction in Stress Levels. The Interviews Highlighted Themes Which Included: Dependence and Autonomy, Progress, Positive Personal Gains and Room for Fine Tuning. Reported Limitations Of the Group Included: the Content, Distractions from Other Participants And Limited Practice Exercises Outside of the Group; Conclusions: Findings Suggest That Inviting Patients to a Mindfulness-based Group Within Rehabilitation Services is Feasible Given the Right Ward Milieu. Benefits May Include Increased Levels of Calmness and an Enhanced Ability To Learn Something New and Feel Part of a Group. We Make Recommendations For Future Ward-based Groups.